Uma arquitetura para distribuição de ambiente virtuais de realidade aumentada - Silva, Wender Antônio da (2008)
This thesis presents an architecture for distribution of virtual environments in Augmented Reality as a tool to support projects in education. Subsequently, according to the evaluators, you can see that the results showed that the prototype is effective and enforceable. In face of this, this work aims creating an interface for interaction with the user and a layer for distribution of made interactions. Thus, for the creation of the software prototype, the interface of Augmented Reality is based on a study case that represents a specific area of knowledge, in this case the plant physiology. Thus was created an interface of Augmented Reality that enables user interaction with the virtual environment through menus for interaction and also by means of labels. This interface is integrated with a layer of distribution. Thus, the layer of distribution was implemented following the methodology client / server-based objects. With the implementation, the interactions made in an environment are replicated for other environments and vice versa, thereby generating a strong system applicable to education as it can provide multiple views of virtual objects on the real objects. The system was submitted and evaluated by teachers and students of a Educational Institution, a Faculty of Itumbiara city, Goiás. Thus teachers and students of information technology and biology areas examined the prototype and answered a questionnaire based on ISONORM. Later, according to the evaluators, it could be seen that the results showed the prototype is effective and enforceable.